Ethnic segregation between Hungarian schools: Long-run trends and geographic distribution - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
Using all of the available data on the ethnic composition of Hungarian primary schools, this paper documents the degree of between-school segregation of Roma versus non-Roma students between 1980 and 2011. We calculate the measures of segregation within school catchment areas as well as within micro-regions and within the larger municipalities (towns and cities). Catchment areas are clusters of villages, towns and cities that are closed in terms of student commuting, and they are defined by us using the observed commuting patterns. Our results show that ethnic segregation between Hungarian schools increased substantially between 1980 and 2011. Segregation appears to have decreased between 2006 and 2008 and increased again afterwards, but the noise in the data prevents us from drawing firm conclusions. In the cross section, school segregation is positively associated with the size of the educational market and the share of Roma students, similar to the results from U.S. metropolitan areas. These relationships strengthened over time in Hungary, and the change in segregation is associated with changes in the number of schools and the share of Roma students.
Keywords: H75; I21; J15; 330; School segregation; Roma minority; disadvantaged students; Schule; Segregation; Ethnische Gruppe; Roma-Bevölkerung; Ungarn